2012
DOI: 10.1186/1743-7075-9-82
|View full text |Cite
|
Sign up to set email alerts
|

A 21-day Daniel fast with or without krill oil supplementation improves anthropometric parameters and the cardiometabolic profile in men and women

Abstract: BackgroundThe Daniel Fast is a vegan diet that prohibits the consumption of animal products, refined foods, white flour, preservatives, additives, sweeteners, flavorings, caffeine, and alcohol. Following this dietary plan for 21 days has been demonstrated to improve blood pressure, LDL-C, and certain markers of oxidative stress, but it has also been shown to lower HDL-C. Krill oil supplementation has been shown to increase HDL-C.MethodsWe investigated the effects of following a Daniel Fast dietary plan with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
2
24
2
Order By: Relevance
“…The present results, for total groups, differ coarsely from those reported with the Daniel Fast (DF) [17,18] and the GOC fast. [4,19,20] Clinical and epidemiological evidences have shown that during the DF and GOC fast both T.…”
Section: Discussioncontrasting
confidence: 83%
“…The present results, for total groups, differ coarsely from those reported with the Daniel Fast (DF) [17,18] and the GOC fast. [4,19,20] Clinical and epidemiological evidences have shown that during the DF and GOC fast both T.…”
Section: Discussioncontrasting
confidence: 83%
“…While participants did not maintain perfect compliance, it appears that approximately 80% compliance is adequate to promote positive changes in the lipid panel. Interestingly, as in past studies of the DF [1,2,4], at the 3 week time period, HDL-C was reduced slightly. However, at the 3 and 6 month time period, values were slightly higher as compared to pre, indicating that the decrease in HDL-C when adopting the DF plan may be transient.…”
Section: Discussionsupporting
confidence: 61%
“…For mood, vitality, and satiety, participants rated each item using a scale of 1-10 (1=as low as possible; 10=as high as possible). These data were based entirely on self-report and we used the same questions as in our prior research of the DF [1][2][3][4].…”
Section: Compliance Subjective Feelings and Satietymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, alteration of whole food intake in favor of nitrate-rich vegetables and low saturated fat/low sugar foods may prove helpful (Bloomer et al, 2011;Trepanowski et al, 2012). In ISSN 2157-6076 2016 addition, a variety of pharmaceutical agents have been used in an attempt to alter NO • production and/or availability.…”
Section: Proposed Methods To Increase Nitric Oxidementioning
confidence: 99%